Pengembangan Aplikasi Mobile Sistem Pengendalian Oven Tembakau Berbasis Internet of Things - Jumawal; Sudianto, Aris; Zulkipli; Putra, Yupi Kuspandi (Fakultas Teknik Universitas Hamzanwadi, 2025)
Tobacco leaf drying is an important process in determining the final quality of tobacco as a raw material for the cigarette industry. This process is generally carried out using a tobacco oven which is influenced by two main factors, namely temperature control and oven ventilation. If the temperature and ventilation settings are wrong, it can reduce the quality of the tobacco leaves produced. To overcome this, this study developed a tobacco oven control system based on the Internet of Things (IoT) which is integrated with a mobile application. This system is designed to monitor and regulate the temperature and open and close the oven ventilation automatically. The DHT11 temperature sensor is used to read the temperature in the oven, while the DC Servo motor is used to control the ventilation. All sensor data is displayed in real-time via an Android application connected to the esp8266 Ethernet module to the Arduino Uno microcontroller. The test results show that the system can run well, where the oven temperature and ventilation control work according to the specified threshold values. In addition, the oven owner can easily monitor the condition of the oven via a mobile application, so that the tobacco leaf drying process becomes more efficient and of higher quality.